REKAYASA MESIN PENGKABUT AIR (HUMIDIFIER CONTROL) UNTUK PENINGKATAN PRODUKSI BIBIT KLENGKENG PINGPONG - Widata, Sri; Gunarso, Gunarso; Nugroho, Fajar; Herahli, Among (Universitas Negeri Yogyakarta, 2011)
This research is aimed to disclose fogging machine application effectiveness for improving klengkeng pingpong seed production. The effectiveness of fogging machine may be measured based on the degree of the fogging machine usage success in klengkeng pingpong nursery process, whose degree of achievement shall be higher than nursery process conducted in natural manner. The research result shows that the average degree of achievement in klengkeng pingpong nursery in way of seedling, top grafting, bridging or marcot, by using fogging machine is 79.26%. Meanwhile klengkeng pingpong nursery process in natural manner is approximately 40%. In return to this, it indicates that fogging machine usage on klengkeng pingpong nursery is deemed effective as it has exceeded successful level of natural klengkeng pingpong nursery. Thus, it may eventually be applied in improving klengkeng pingpong seed production